Orgulho e Preconceito de Jane Austen: literatura e sociedade patriarcal em sua tradução brasileira - Soares, Aline Benato (2016)
This research developed a descriptive study about the work of Jane Austen's Pride and Prejudice, in relation to social literary studies in the nineteenth century patriarchal society. In addition, the paratexts of some Brazilian translations of the work were analyzed in order to analyze the reception of the book in the Brazilian literary polysystem. Also, an analysis of two translations of the book Pride and Prejudice was carried out, having as basis of analysis the source text published in 1813. For the realization of this research was used the theoretical support of the studies of Virginia Woolf (1998) and Julia Prewitt Brown (1985) with regard to the study of the patriarchal society of the time. For the paratextual analysis we used the studies of Gerard Genette (2006) that states that the paratexts that accompany a work are extremely important for its interpretation. For the analysis of the reception of the book in the Brazilian literary polysystem, were used the studies of Itamar Even-Zohar (1990) and his Theory of Polysystems. And finally, for the Brazilian translation analyzes, were used the studies of Gideon Toury (2012), with Descriptive Studies of Translation, and the studies of José Lambert and Hendrik Van Gorp (2006) and their scheme for the analysis of translations. And the analyzes of Andre Lefevere (1992) regarding discussions about translation politics. It was found that the context in which Jane Austen lived influenced her work, and in Pride and Prejudice the author denounces the aristocratic customs of nineteenth-century patriarchal society. The work of Jane Austen was consolidated in the Brazilian literary polysystem, which we can perceive through the paratexts of the translations launched in Brazil. The translation of the work into Brazilian Portuguese reveals differences between the translation procedures adopted, one translation being considered more "foreign" and the other more "domesticated" according to Lawrence Venuti's theory (2002). Finally, the analyzes carried out show us how the author was consolidated in the Brazilian literary polysystem and remains valued even over the centuries.